Effect of Curry Spice (Murraya Koenigii) On the Shelflife of Cookies (Biscuit) Produce from Sorghum Flour Blends with Wheat Flour (Global Journal of Science Frontier Research, 2012)
Melon flour was blends with Wheat flour in the following ratio 100:0, 70:30,50:50, 30:70,0:100 and each categories were spiced with ginger (Zingiber officinale) at concentration of 5g and 10g respectively. The effect of spice (Zingiber officinale) at both concentration (5g and 10g) on the physical properties height, diameter were determined for all categories using meter rule and then spread factor was calculated to range from 2.8X102 to 14.8 X102. Microbial evaluation was carried out on the prepared cookies. Total Viable Count, Total Staphylococcus count, Total Bacillus count and Total coliform count were determined using selective media. These were comparing to microbiological specification for baked cookies. The effect of the spice Zingiber officinale at both concentrations on the microbial load reveals a significant difference as increase in the spice concentration led to decrease in microbial load.
Keywords: Microbial Load; Organoleptic Properties; Shelf Life